KONSEP PEMIMPIN IDEAL DALAM SYI'IR MADAH JARIR (Telaah Strukturalisme Puisi Pujian Jarir Terhadap Umar Ibn Abdul Aziz) - Ahmad Kholil (El-QUDWAH, 2010)
There are two elements in every literary works, intrinsic and extrinsic. Structuralism used as the tool for analyzing Jarir’s work here is the intrinsic one. By using this approach, the ideal concept of leadership founded here are: responsibility, empathy, ability to rule with correct system, morality, ability to communicate with all elements, modest in anything related to physichal beatifulness, keeping well performance.From elements which form the intrinsic aspects, the structure of this Jarir’s madah poetry is really strong. There are three aspects that support the strength of intrinsic structure, they are unity as intern coherence, transformation as the new formula and self regulation. Beside theme, this poetry have plot, character and characterization, and setting. The relation between the process of plot and conflict is really close. Character develop together with conflict. There are some characters, one of them is kholifah that become the character and goal of this poetry. There are also the explanation about characteristic of character and condition of the people strike with poverty. This poetry use usual words but soft, this makes it easily to be understood. Since madah is for praise Kholifah to get our goal.